2017
DOI: 10.1021/acsami.7b12918
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Permeable, MMP-2 Activatable, Nickel Ferrite and His-Tagged Fusion Protein Self-Assembled Fluorescent Nanoprobe for Tumor Magnetic-Targeting and Imaging

Abstract: Matrix metalloproteinases (MMPs) activatable imaging probe has been explored for tumor detection. However, activation of the probe is mainly done in the extracellular space without intracellular uptake of the probe for more sensitivity. Although cell-penetrating peptides (CPPs) have been demonstrated to enable intracellular delivery of the imaging probe, they nevertheless encounter off-target delivery of the cargos to normal tissues. Herein, we have developed a dual MMP-2-activatable and tumor cell-permeable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The upregulated levels of MMP enzymes in TME makes them the most common target for enzyme-based TME nanoparticles. Sun et al [ 47 ] reported the development of MMP-2 activatable nanoprobes, which can be used for selective and specific intracellular imaging of the tumor (Fig. 3 ).…”
Section: Targeting Of Common Attributes Of Tmementioning
confidence: 99%
“…The upregulated levels of MMP enzymes in TME makes them the most common target for enzyme-based TME nanoparticles. Sun et al [ 47 ] reported the development of MMP-2 activatable nanoprobes, which can be used for selective and specific intracellular imaging of the tumor (Fig. 3 ).…”
Section: Targeting Of Common Attributes Of Tmementioning
confidence: 99%
“…The nickel ferrite (NF) compound, NiFe 2 O 4 , is a well-known inverse spinel including Ni 2+ and Fe 3+ ions distributed between the octahedral and tetrahedral sites, respectively . There are many reports about the use of nickel ferrite such as biomedical, electric, and electronic devices, ferro-fluids, magnetic refrigeration, color imaging, and microwave devices. − Also, there are many techniques like citric acid combustion, organic gel-thermal decomposition, sol–gel autocombustion, hydrothermal process, thermolysis, co-precipitation, gel-assistant hydrothermal process, self-propagation, and use of microemulsion for the preparation of nanocrystallite NF. − Amongst the reported techniques for the preparation of NF nanostructures, the microwave technique has gathered the most attention because of some benefits such as feasibility, inexpensiveness, environmental friendliness, and short reaction time …”
Section: Introductionmentioning
confidence: 99%
“…MMP-activatable CPPs also enhance the specificity in tumor imaging. Taking advantage of the over-expressed MMP-2 enzyme, Sun et al designed an MMP-2 activatable, cell permeable magnetic nanoprobe in which the fluorescence doner (mCherry fusion protein) and fluorescence quencher (a nickel ferrite NP) were conjugated with MMP-2 substrate peptide [58] . MMP-sensitive PEG cleavable strategy has endowed CPP-NPs with both stealth circulation and in time targeted cellular internalization, especially in tumor treatment.…”
Section: Multifunctional Cppsmentioning
confidence: 99%